Nitrogen in browse species: Ruminal degradability and post-ruminal digestibility measured by mobile nylon bag and in vitro techniques - Kaitho, R.J.; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van (Wiley, 1998)
This study determined nitrogen degradability and digestibility of rumen undegradable nitrogen using mobile nylon bag (MNB) and pepsin/pancreatin in vitro technique (IV) of 40 browse species. Thirty Ethiopian highland sheep fitted with rumen cannulae were used in nitrogen (N) degradability studies. Six steers fitted with rumen cannulae were used in preparation of 16-h and 24-h ruminal undegraded residues and four steers fitted with distal abomasal cannulae were used in MNB technique. The browses varied widely in nitrogen solubility (15-468 g kg-1), potential degradability (223-976 g kg-1), rate of degradation (0.13-24 percent h-1) and effective degradability (135-821 kg-1). The apparent N digestibility (ND) of the rumen undegraded residues differed significantly (P<0.05) among browse species. No significant difference (P>0.05) was observed in ND of 16-h and 24-h residues. The ND of the 16-h residue varied from -218 to 759 g kg-1 and 169 to 851 g kg-1 for MNB and IV methods, respectively. Browse species with high tannin contents such as Acacia hockii, A horrida, A melanoxylon, A persiciflora, A salicina, A saligna and Flemingia macrophylla had high rumen by-pass and a low ND, while Sesbania spp and A nilotica with low tannin contents underwent rapid and extensive dry matter and nitrogen degradation in the rumen. Acacia sieberiana, Chamaecytisus palmensis, Erythrina spp, Gliricidia sepium, Samanea saman and Enterolobium cyclocarpum had high proportions of protein escaping rumen degradation (BP) and with a high proportion of the by-pass protein digested in the intestine, therefore these browses had a high potential as protein supplements. The ND measured with the MNB were significantly lower (P<0.001) than by the IV method. The correlation between MNB and IV was high and significant (R2=0.89, P<0.0001) as also indicated by the regression equation (SE in parentheses): MNB = -22.8 (4.55) + 1.0 (0.08)IV (RSD = 10.56, R2=0.79, n=40, P<0.001). The intercept of the linear relationship obtained was different from zero while the slope was not different from unity. Multiple regression analysis suggested that some of the unexplained variation could be accounted for by either nitrogen, acid detergent fibre, total phenolics or neutral detergent fibre bound tannin levels in browses. The IV method is accurate for estimating digestibility of ruminally undegradable N, and hence its use would considerably reduce the need for delicate surgery and the elaborate procedures involving the MNB technique.